Administration of Different Doses of Basil Leaf Extract (Ocimum Sp.) as a Preventive Measure Against Disease in the Survival of 7-Day-Old Pearl Catfish (Clarias Gariepinus) Seeds - Floranda Rahmadheny Gandesha; Didik Budiyanto; Sumaryam; Retnani Rahmiati; Kejora Handarini (International Journal Labs, 2026)
This study aims to determine the ability of basil leaf extract as a disease prevention measure in pearl catfish seeds aged 7 days. The research was conducted using experimental methods. The experimental design used was a Completely Randomized Design (CRD) with one factor, namely the difference in the dose of basil leaf extract, which consisted of six treatments with four replicates. The treatment tested was the difference in the dosage of basil leaf extract, namely treatment A (0 mL), B (20 mL), C (30 mL), D (40 mL), E (50 mL), and F (60 mL), in 3 L of rearing water. The data were analyzed using ANOVA. The test animals used were pearl catfish (Clarias gariepinus) aged 7 days that were indicated to be sick. The results of the study showed that the administration of basil leaf extract had a significant effect as a disease prevention measure on the survival of pearl catfish seeds aged 7 days, with the highest survival rate reaching 82.5%. The optimal dose of basil leaf extract as a disease prevention measure was the administration of 30 mL/3 L of basil leaf extract (Treatment C). Water quality data were still supportive of the growth of catfish seeds, with pH values ranging from 6.08–7.08, dissolved oxygen ranging from 3.07–4.00 mg/L, and a temperature of around 27.7 °C, which is still within the water quality standard for fish rearing, except for ammonia levels ranging from 0.13–0.44 mg/L, which exceed the optimum water quality standard.